2019
DOI: 10.1101/637223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The nucleosome acidic patch directly interacts with subunits of the Paf1 and FACT complexes and controls chromatin architecture in vivo

Abstract: The nucleosome core regulates DNA-templated processes through the highly conserved nucleosome acidic patch. While structural and biochemical studies have shown that the acidic patch controls chromatin factor binding and activity, few studies have elucidated its functions in vivo. We employed site-specific crosslinking to identify proteins that directly bind the acidic patch in Saccharomyces cerevisiae and demonstrated crosslinking of histone H2A to Paf1 complex subunit Rtf1 and FACT subunit Spt16. Rtf1 bound t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Despite their related functions, Spt6 and FACT clearly have independent, non-redundant roles, since both are essential for viability, as well as divergent biochemical activities, unique aspects of interactions with nucleosomes, and distinct patterns of recruitment to chromatin (Duina, 2011;Mayer et al, 2010;McCullough et al, 2015;Pathak et al, 2018). While one of the main mechanisms for recruitment of Spt6 to chromatin is by its interaction with RNAPII (Dronamraju et al, 2018;Mayer et al, 2010;Sdano et al, 2017), the recruitment mechanism for FACT is less clear and likely depends on multiple mechanisms, including interactions with histones (Cucinotta et al, 2019;Hodges et al, 2017), histone H2B ubiquitylation (Fleming et al, 2008;Murawska et al, 2020), and by the recognition of altered nucleosome structure (Martin et al, 2018). Thus, studies of Spt6, Spn1, and FACT have revealed intriguing relationships between the three and raised the question of how they interact during transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their related functions, Spt6 and FACT clearly have independent, non-redundant roles, since both are essential for viability, as well as divergent biochemical activities, unique aspects of interactions with nucleosomes, and distinct patterns of recruitment to chromatin (Duina, 2011;Mayer et al, 2010;McCullough et al, 2015;Pathak et al, 2018). While one of the main mechanisms for recruitment of Spt6 to chromatin is by its interaction with RNAPII (Dronamraju et al, 2018;Mayer et al, 2010;Sdano et al, 2017), the recruitment mechanism for FACT is less clear and likely depends on multiple mechanisms, including interactions with histones (Cucinotta et al, 2019;Hodges et al, 2017), histone H2B ubiquitylation (Fleming et al, 2008;Murawska et al, 2020), and by the recognition of altered nucleosome structure (Martin et al, 2018). Thus, studies of Spt6, Spn1, and FACT have revealed intriguing relationships between the three and raised the question of how they interact during transcription.…”
Section: Introductionmentioning
confidence: 99%
“…To probe the role of nucleosome order in establishing islands and deserts, we analyzed mutants lacking the PAF1C subunit Rtf1, which has been implicated in nucleosome positioning and affects meiotic DSB activity (36,37). MNase-seq analysis of rtf1 Δ mutants revealed reduced nucleosome order along genes, as indicated by the less pronounced periodicity of nucleosome peaks in islands relative to the +1 nucleosome ( Figure S5H-I ).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the 30-nm fibers which are strongly contributed by H4 tail to acidic patch interactions, liquid-like chromatin is instead stabilized by a diverse range of non-specific DNA-histone tail electrostatic interactions. Therefore, within liquid-like chromatin the nucleosome acidic patch region can be more easily accessed by the myriad of chromatin-binding factors that have been proposed to target it in vivo 112,123 , which include HP1 124 . Furthermore, controlled access to the acidic patch region has been hypothesized to play a crucial role in the modulation of chromatin remodelling motors that regulate nucleosome sliding 125 .…”
Section: Discussionmentioning
confidence: 99%